Hospital admissions and financial impact due to Pulmonary Tuberculosis in Bahia, Brazil - Souza Júnior, Edison Vitório de (2018)
The purpose of this study was to describe the cases of hospital admissions and the financial impact of pulmonary tuberculosis in the state of Bahia, Brazil between 2012 and 2016. It is an epidemiological, descriptive and cross-sectional study, using the data obtained in the Department of Information Technology of the Unified Health System. The variables collected were: sex, age group, values of hospital services and race, reported in the period of 2012 and 2016. The cases of hospital admissions have been selected in accordance with chapter I of the 10th International Statistical Classification of Diseases and Health Problems, including the categories between A15.0 and A15.3. Among the results, it was found that in the period studied, 5,593 cases of hospital admissions for pulmonary tuberculosis in the state of Bahia were registered, which corresponds to 0.14% of the total number of hospitalizations. The highest prevalence occurred in the Eastern macro region (n = 4,623), between male people (n = 4,079), between 40 and 49 years old (n = 1,361) and color / race ignored (n = 5,176). Pulmonary tuberculosis has generated a financial impact in Bahia of more than 7 million reales in the period studied and the Eastern macro region has generated greater spending to the state, corresponding to 91.70% of total hospital costs. It is concluded that in the Eastern macro region, the mode of distribution of cases of hospital admissions for pulmonary tuberculosis makes the macro region a priority for the actions of control and prevention of the pathology.